Molecular tools in understanding the evolution of Vibrio cholerae - Rahaman, Md. Habibur; Islam, Tarequl; Colwell, Rita R.; Alam, Munirul (Frontiers in Microbiology, 2015)
Vibrio cholerae, the etiological agent of cholera, has been a scourge for centuries. Cholera remains a serious health threat for developing countries and has been responsible for millions of deaths globally over the past 200 years. Identification of V. cholerae has been accomplished using a variety of methods, ranging from phenotypic strategies to DNA based molecular typing and currently whole genomic approaches. This array of methods has been adopted in epidemiological investigations, either singly or in the aggregate, and more recently for evolutionary analyses of V. cholerae. Because the new technologies have been developed at an ever increasing pace, this review of the range of fingerprinting strategies, their relative advantages and limitations, and cholera case studies was undertaken. The task was challenging, considering the vast amount of the information available. To assist the study, key references representative of several areas of research are provided with the intent to provide readers with a comprehensive view of recent advances in the molecular epidemiology of V. cholerae. Suggestions for ways to obviate many of the current limitations of typing techniques are also provided. In summary, a comparative report has been prepared that includes the range from traditional typing to whole genomic strategies.